Research Activity as an Integral Component of Engineering Education; Ponte; Vol. 72, iss. 4 - Kuimova M. V. Marina Valerievna; Burleigh D. Douglas; Arnst Yu. Yu. Yuliya Yurjevna; Sentsov A. E. Arkady Eduardovich (2016, 2016)
Title screen